Advances in Comparative Endocrinology - Navarro, Isabel; Gutiérrez, Joaquim; Capilla, Encarnación (Publicacions i Edicions de la Universitat de Barcelona, 2015)
The present volume of the series Advances in Comparative Endocrinology contains the contributions of the participants of the 9th Congress of the "Asociación Ibérica de Endocrinología Comparada" (AIEC) that took place at the University of Barcelona in July 2013. This volume includes a great variety of studies of prestigious and international recognized research groups using vertebrate and invertebrate species, contributing with the most recent insights related to the hormonal control of important physiological processes such us growth, development, food intake, metabolism, stress and reproduction among others.